Pengaruh Dukungan Sosial dan Kecerdasan Emosi Terhadap Kesejahteraan Psikologis dengan Resiliensi Sebagai Variabel Mediasi pada Organisasi X - Willy Adimas Rahmawan; Hardani Widhiastuti; Rusmalia Dewi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the effect of social support and emotional intelligence on psychological well-being with resilience as a mediating variable in organization X. The research sample was taken using the Accidental sampling technique. The research sample was taken using a social support scale, an emotional intelligence scale, and a resilience scale. Data analysis using the SmartPLS program. Data collection was carried out through a questionnaire distributed online using Google Form conducted on personnel of the Yogyakarta Special Region Police with the Accidental sampling technique. Data analysis used SmartPLS to test validity, reliability, and hypothesis. The results showed that social support had a positive and significant effect on psychological well-being. Emotional intelligence had a positive and significant effect on psychological well-being. Resilience had a positive and significant effect on psychological well-being. Social support had an effect on resilience, as well as emotional intelligence had a positive and significant effect on resilience. Resilience partially mediates the effect of social support and emotional intelligence on psychological well-being. This means that good social support, emotional intelligence, and resilience can improve psychological well-being. This study has implications for increasing social support and emotional intelligence and resilience with psychological well-being.